Applications of parallel processing algorithms for DNA sequence analysis. - Collins, J F (1984)
Programs have been written to apply parallel processing algorithms to the main methods of DNA sequence analysis. These programs allow the largest of currently interesting problems to be handled on a medium-sized computer system. The abundance of information otherwise not readily available has suggested new methods for the detection of homology and order in sequences.